2019
DOI: 10.1021/acsami.8b22214
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Hydrogen Boride Monolayers as Potassium-Ion Battery Anodes for Wearable Electronics

Abstract: The rapid development of wearable electronics has revealed an urgent need for low-cost, highly flexible, and high-capacity power sources. In this sense, emerging rechargeable potassium-ion batteries (KIBs) are promising candidates owing to their abundant resources, low cost, and lower redox potential in nonaqueous electrolytes compared to lithium-ion batteries. However, the fabrication of flexible KIBs remains highly challenging because of the lack of high-performance flexible electrode materials. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 56 publications
3
50
1
Order By: Relevance
“…The situation for K + storage is similar to that of Na + 2b. Density functional theory (DFT) calculations have revealed that H‐vacancies in a curved BH monolayer lower the migration energy barrier of K + ions on the boron‐concave side to E bar (0.03–0.28 eV) relative to that of pristine BH (0.32 eV), which decreases even further with proximity to the H vacancy (Figure c,d) 41a. Note that the structural features of a BH monolayer are more similar to an M a X b structure than to a X a Y b structure.…”
Section: Energy‐related Applicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…The situation for K + storage is similar to that of Na + 2b. Density functional theory (DFT) calculations have revealed that H‐vacancies in a curved BH monolayer lower the migration energy barrier of K + ions on the boron‐concave side to E bar (0.03–0.28 eV) relative to that of pristine BH (0.32 eV), which decreases even further with proximity to the H vacancy (Figure c,d) 41a. Note that the structural features of a BH monolayer are more similar to an M a X b structure than to a X a Y b structure.…”
Section: Energy‐related Applicationsmentioning
confidence: 75%
“…Several emerging energy‐related electrocatalytic reactions, such as carbon dioxide reduction and nitrogen fixation, have recently received close attention due to their potential for clean and convenient energy production and/or storage. The unique characteristics of ultrathin 2D materials with X a &X a Y b , M a X b , and M a X b Y c structures are well‐suited for these applications. In addition, depending on the structure of these materials, vacancy engineering can be used to fine‐tune or tailor properties according to the specific needs of the application.…”
Section: Energy‐related Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 53 ] The elastic constants are listed in Table S1 in the Supporting Information and the elastic moduli is 300.65 and 221.44 N m −1 in the a and b direction, respectively. These exceeds those of hydrogen boride (BH) monolayer (157 and 109 N m −1 ), [ 54 ] MoS 2 (133 and 133 N m −1 ), [ 55 ] β 12 borophene (123 and 147 N m −1 ). [ 56 ] And the elastic constant of a direction is even close to graphene (342 N m −1 in the a direction).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a 3 × 3 × 1 graphene supercell could hold four layers of K atoms with a total 12 atoms, corresponding to the stoichiometric ratio of K 2 C 3 and a maximum K capacity on defect‐free graphene of 1487.7 mA h g −1 . The capacity is larger than most 2D electrodes, such as Θ‐graphene (956 mA h g −1 ), [ 14 ] xgraphene (744 mA h g −1 ), [ 15 ] hydrogen boride (1138 mA h g −1 ), [ 16 ] blue phosphorene (865 mA h g −1 ), [ 17 ] VS 2 (466 mA h g −1 ), [ 13 ] Ti 3 C 2 (192 mA h g −1 ), [ 18 ] and MoN 2 (432 mA h g −1 ). [ 19 ] Such a high specific capacity may be attributed to the multilayer adsorption of K atoms and light weight of C atoms.…”
Section: Resultsmentioning
confidence: 99%